Concentração proprietária dos meios de comunicação de massas na democracia constitucional - Menezes Neto, Elias Jacob de (Universidade do Vale do Rio dos Sinos, 2012)
The main hypothesis of this work if the idea that concentrated ownership of mass media is incompatible with constitutional democracy and fundamental rights. Through the literature review, three analyses will be made in each chapter. Altogether, they aim to reflect upon the central role of the fourth power within contemporary societies, as well to question how concentrated ownership of media thwarts political pluralism and democracy. In this vein, the first chapter will focus on freedom of expression. After a brief historical and theoretical approach of the most commonly used theories, this work will use the axiomatic legal theory, by Luigi Ferrajoli, as a keystone to understand fundamental rights. This approach was chosen because, in addition to its obvious connection withthe legal garantism, it emphasises the distinction between fundamental rights and property rights. The second chapter will correlates democracy to the need of visible and pluralistic forms of power within the public sphere. To do so, two ideas about the democratic regime will be opposed: firstly, the so called “purely formal”, by Norberto Bobbio, establishes minimum standards for the “democratic game”; the second, by Luigi Ferrajoli, will be named “constitutional democracy theory” since it has, as main feature, the inclusion of fundamental rights as a substantial side to the very concept of democracy. Both theories share a common urge to discuss the possibility to form a plural public opinion, which will be discussed based on the idea of Jürgen Habermas’ political public sphere. The third chapter will show the problem of concentrated ownership of mass media and the link between the exercise of media power and the ‘(de) constituent process’, especially based on perspectives of Luigi Ferrajoli, John B. Thompson and C. Edwin Baker. After proposing ideas for the reformulation of the media industry, it will be concluded that the control of mass media’s ownership is just one of several ways to protect freedom of expression and to expand democracy to the largest number of realms of life.
Keywords: Liberdade de expressão; Democracia constitucional; Meios de comunicação de massas; Esfera pública; Freedom of expression; Constitutional democracy; Mass media; Public sphere; ACCNPQ::Ciências Sociais Aplicadas::Direito